Malaria : obstacles and opportunities - Institute of Medicine (U.S.), Committe for the study on malaria prevention and control : status review and atternative strategies; Oaks, Stanley C.; Mitchell, Violaine S.; Pearson, Greg W.; Carpenter, Charles C. J. (Charles Colcock J.) (Washington, D.C. : National Academy Pr, 1991)
42